New materialisms and children’s outdoor environments: murmurative diffractions - Merewether, Jane (Routledge, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group This article draws on new materialisms to highlight children’s sensitivity to the agency of nonhuman materials. Working with data fragments from an ongoing project investigating children’s relationship with their outdoor environments, the article uses the figure of murmuration in a diffractive analysis approach to reveal materialdiscursive intra-actions. In doing so, the article highlights an ingrained tendency to focus on the human whilst overlooking the material. Attentiveness to the agency of all matter, human and nonhuman, has significant implications for early childhood geographies, research and pedagogy as it shines a light on the intra-active nature of the world. This offers new possibilities but also calls attention to the relations of responsibilities inherent in a world where all matter is vibrant and agential.